Społeczna odpowiedzialność w relacjach międzysektorowych - Szymankiewicz, Maria Janina (Annales. Etyka w Życiu Gospodarczym, 2015)
The performance and development of an organisation depends not only on the organisationitself, but – to an increasing extent – on its relationships with its surroundings.This also refers to cross-sector relationships outside the world of business. Thus, thepurpose of the article is to analyse the cross-sector collaboration between public administrationand non-governmental organisations (NGOs), and to highlight its fundamentalterms and conditions, e.g. trust and social responsibility. The more honestythere is in such relations, the more trust and willingness to co-operate there arisesin both parties. The analysed model of collaboration between public administrationand NGOs seems to be a helpful tool for the development of collaboration based onsocial responsibility.